2005
DOI: 10.1590/s1517-86922005000500006
|View full text |Cite
|
Sign up to set email alerts
|

Influência da utilização da órtese de tornozelo durante atividades do voleibol: avaliação eletromiográfica

Abstract: The ankle sprain is the most frequently found acute injury in volleyball. Aiming to prevent the occurrence of ankle injuries, prophylactic equipment as the bracing had been developed. This study had the purpose to evaluate the performance of the ankle muscles (tibialis anterior, peroneous longus, and medial and lateral gastrocnemius) by measuring the electrical activity in different volleyball activities (vertical jumping and lateral shuffling) with and without using ankle bracing. Nine young female volleyball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
4
0
6
Order By: Relevance
“…In this regard, the mechanism of the bracing effect on the ankle muscles activity has been evaluated. Few researchers have investigated the effect of bracing on the ankle muscles during different tasks [4][5][6][7] and reported contradictory results. Hopper and et al investigated the effect of bracing on the selected muscle activity in netball players in jump landing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the mechanism of the bracing effect on the ankle muscles activity has been evaluated. Few researchers have investigated the effect of bracing on the ankle muscles during different tasks [4][5][6][7] and reported contradictory results. Hopper and et al investigated the effect of bracing on the selected muscle activity in netball players in jump landing.…”
Section: Introductionmentioning
confidence: 99%
“…Cardoso et al indicated that ankle bracing cannot affect the muscles activity during vertical jumping and lateral shuffling [4]. Tesuchida et al reported the effect of bracing on the activity of selected muscles during landing from 30 cm and 50 cm height movements.…”
Section: Introductionmentioning
confidence: 99%
“…Esta modalidade tem como gestos esportivos uma grande quantidade de saltos repetitivos, em diversos movimentos como o de defesa (bloqueio), os movimentos de armação de jogadas (levantamento) e os movimentos de ataque (saque e finalização das jogadas) 1,2 . Os saltos por sua vez são gestos que no retorno ao solo podem provocar uma inadequada aterrissagem e provocar lesões como as entorses 3,4 Esses gestos tornam-se uma ameaça as articulações dos atletas devido a característica desse esporte ser de uma modalidade que muitas vezes permite o contato entre atletas [1][2][3] . É nesse contato que muitas vezes aparecem as lesões, sendo a entorse a lesão mais frequente e o tornozelo a articulação mais acometida quando comparada com as outras articulações 1,4 .…”
Section: Introductionunclassified
“…Os saltos por sua vez são gestos que no retorno ao solo podem provocar uma inadequada aterrissagem e provocar lesões como as entorses 3,4 Esses gestos tornam-se uma ameaça as articulações dos atletas devido a característica desse esporte ser de uma modalidade que muitas vezes permite o contato entre atletas [1][2][3] . É nesse contato que muitas vezes aparecem as lesões, sendo a entorse a lesão mais frequente e o tornozelo a articulação mais acometida quando comparada com as outras articulações 1,4 . As entorses correspondem a quase 80% dessas lesões e o mecanismo por inversão chega a 90% 5 .…”
Section: Introductionunclassified
“…The volunteers jumped with countermovement, as high as possible with the aid of the arms during the impulse phase, in a total of five attempts (Cardoso et al, 2005).…”
Section: Vertical Jumpmentioning
confidence: 99%